Maternal and neonatal outcomes of in-water and out-of-water births in low-obstetric-risk labour: a retrospective observational study at Piacenza hospital. - Piccolo, Elisa; Biasucci, Giacomo; Magistrali, Mariasole; Benenati, Belinda; Russo, Daniela; Mercati, Marina Paola; Tesoriati, Sonia; Cicalla, Marina; Illari, Simona; Pavesi, Cristiana; et al. (Journal of Biomedical Practitioners, 2025)
INTRODUCTION The utilisation of birth pool immersion during labour and delivery constitutes one of the primary non-pharmacological methods for alleviating pain. Consequently, an increasing number of women are opting to employ aquatic environments as a means of managing the childbirth experience. However, the literature reports conflicting data and poor-quality evidence on maternal and neonatal outcomes. It becomes important to understand whether water birth is safe for both woman and baby. The objective of this research is to evaluate and compare neonatal outcomes, including infections, admission to the neonatal intensive care unit, and Apgar scores at one and five minutes, alongside maternal outcomes such as vagino-perineal lacerations, postpartum haemorrhage, the duration of labour and the expulsive phase, as well as infections, between water birth and non-water birth scenarios. METHODS A retrospective observational cohort study employing a parallel design was undertaken. A total of 698 women with low-risk obstetric pregnancies were included and stratified into two groups based on the type of delivery. Data analysis was performed using STATA 16.0 software, applying both descriptive and inferential statistical methods to assess the study variables. A logistic model was created for the study population to identify which variables may contribute to an increased likelihood of injury to the perineum. RESULTS The research sample comprised 698 deliveries, which were evenly distributed between the two cohorts. The groups exhibited homogeneity concerning maternal age, parity, administration of antibiotic treatment during labour, and positivity rates of vaginal-rectal swabs. A further notable discrepancy (p<0.05) was observed in the volume of postpartum blood loss; however, the difference was minimal in both cohorts. Logistic regression analysis revealed that for each 1 cm increase in infant head circumference, the risk of perineal injury increased by 1.3 times (OR = 1.27; p = 0.002). CONCLUSIONS The study identified no significant differences in maternal and neonatal outcomes between water and non-water births. Consequently, it appears both suitable and prudent to permit women experiencing low-risk obstetric labour the autonomy to decide whether to deliver in a water-based setting or not. However, further studies are needed. Despite the findings presented, it is crucial to emphasise that further investigation and analysis are absolutely necessary.